CULEG PERSPECTIVE: PERFORMANCE OF CREDIT UNION COOPERATIVES FEDERATION PUSKOPCUINA - Padang, Laurence Tombi; Asri, Marselinus (Contemporary Journal on Business and Accounting, 2023)
Purpose – This Study aim to test governance variables based on perspective Credit Union Label of Excellence in Governance (CULEG) is governance standards and instruments _measurement Cooperative Credit Union developed by the Asian Confederation of Credit Union (ACCU) for made guidelines for creation score for its members and community the place they operate to CU performance. Design/methodology/approach – Using deep CU sample data scope puskopditcuina in Indonesia, research this prove exists impact application of CULEG to Performance. Findings – Participation influential, and transparency negative and significant to performance cooperative Credit Unions in federation Puskopcuina. Honor Rules, Policies, and Regulations (principle compliance) effect significant and positive to performance cooperative Credit Unions. Originality – Using deep CU sample data scope puskopditcuina in Indonesia, research this prove exists impact application of CULEG to Performance. Keywords: CULEG Perspective, Credit Union, Federation Paper Type Research Result